RISK OF WATER SHORTAGE IN THE WEST REGION OF RIO GRANDE DO NORTE, BRAZIL - Troleis, Adriano Lima; Macedo, Yuri Marques de; França, Vinnícius Vale Dionízio (Geosaberes; Vol 11 (2020): Vol 11 (2020)DO - 10.26895/geosaberes.v11i0.1074, 2020)
The present work is part of a doctoral thesis, which aims to analyse the risk of water shortages in Rio Grande do Norte (RN) using the Water Shortages Risk Index (IRDH) as reference. This research is ushered by the hypothesis that the relationship among some factors (environment, infrastructure, socioeconomic status and state planning) produces territories at risk of water shortages in the State. In this context, in a systemic perspective the index was structured: 19 variables, which correspond to 4 indicators inherent to this hypothesis present factors, were taken into consideration. This work presents the IRDH that belongs to the west water supply region in Rio Grande do Norte. There are 16 municipality in that region, six of them were classified at 'high risk' of water shortages; seven at ‘medium risk’; and three considered at 'low risk' according to the IRDH classification.